Advanced multilayer composite dressing with co-delivery of gelsevirine and silk fibroin for burn wound healing. (15th March 2023) - Sun, Xiaochen; Zhang, Yi; Cui, Jin; Zhang, Chenxi; Xing, Chunlei; Bian, Huihui; Lv, Juan; Chen, Dagui; Xiao, Lan; Su, Jiacan; Liu, Yuanyuan; Su, Li
Abstract: Burn is one of the most common types of injuries worldwide, which remains a clinical challenge due to its progressive exacerbation caused by inflammation and edema that impede the growth and differentiation of fibroblast. To solve this problem, in this study, the anti-inflammatory Gelsvirine (Gs), as a specific STING inhibitor for rheumatoid arthritis pain, is used for inflammation control in burn wound healing. Meanwhile, to improve fibroblast migration, proliferation, and differentiation, the natural protein silk fibroin (SF) was used due to its demonstrated capacity to promote the proliferation of epidermal cells and fibroblasts, facilitate collagen synthesis and further improve wound repair. Through our rational design, a functional dressing for the co-delivery of Gs and SF is developed to improve burn wound healing. A multilayer composite dressing of Polycaprolactone(PCL)/Gs-loaded sodium alginate (SA)/SF-gelatin (Gs@SFD) was prepared using the combination of electrospinning and extrusion method, which contained four layers: PCL-dense barrier layer (to prevent infection), SA-hydrogel layer (to load Gs and keep wound moisture), PCL-loosen support layer (to prevent deformation of bioactive layer and to facilitate Gs release into trauma) and SF/gelatin bioactive layer (to contact with trauma and bioactively induce wound healing). Our data showed that the hydrogel layer realized the sustained release of Gs. As a specific inhibitor of STING signaling pathway, the released Gs inhibited the inflammatory response of macrophages and further reduced the fibroblast damage both in vitro and in vivo . In addition, the bioactive layer promoted cell proliferation, facilitated collagen synthesis, and further improved wound healing in animal model of burn trauma. Therefore, this study provides a novel multilayer composite dressing (Gs@SFD) to facilitate burn wound healing via efficient inflammation control with the sustained release of Gs, and improvement on wound healing due to the bioactive components of silk fibroin, which could serve as a potential therapeutic approach in the future. In addition, our multilayer dressing design provides an advanced drug delivery strategy for burn wound healing.